1992
DOI: 10.1104/pp.98.4.1391
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid and the Maturation of Cacao Embryos in Vitro

Abstract: Abscisic acid (ABA) was tested for its ability to affect development of immature zygotic embryos of cacao (Theobroma cacao) in vitro, by adding exogenous ABA, fluridone, or mefluidide to cultured embryos. Endogenous ABA levels, measured by enzyme-linked immunosorbent assay, were increased by exogenous ABA or by culture on sucrose increasing to 21%, and were decreased by fluridone and, to a lesser extent, by mefluidide. The effects of these on maturation were measured as effects on anthocyanins, lipids, and fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Coincidently, the ABA concentration was relatively low. ABA is an effective inhibitor of germination in immature wheat (Triticum aestivum L.) grain (Walker-Simmons, 1987), cacao (Theobroma cacao L.) embryos (Pence, 1992), and rape (Brassica rapa L.) seed (Finkelstein and Crouch, 1986). In orchids, it has been suggested that high concentrations of ABA occur in seeds that are difficult to germinate such as E. helleborine (Van der Kinderen, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Coincidently, the ABA concentration was relatively low. ABA is an effective inhibitor of germination in immature wheat (Triticum aestivum L.) grain (Walker-Simmons, 1987), cacao (Theobroma cacao L.) embryos (Pence, 1992), and rape (Brassica rapa L.) seed (Finkelstein and Crouch, 1986). In orchids, it has been suggested that high concentrations of ABA occur in seeds that are difficult to germinate such as E. helleborine (Van der Kinderen, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Etienne et al (1993) observed that germination of recalcitrant somatic embryos of Hevea brasiliensis (rubber) was promoted by high concentrations of sucrose and ABA (100-1000 #M) in the plant growth medium, and that these somatic embryos acquired a degree of desiccation tolerance similar to that reported with orthodox embryos (Carman, 1988;Welbaum et al, 1990). Pence (1992) demonstrated that endogenous ABA levels in maturing cacao embryos corresponded with increased production of lipids and fatty acid saturation. She also noted that moisture levels drop from 90% in prematuration embryos to 30% in mature cacao embryos, but that the embryos lack desiccation tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…ABA has also been shown to regulate the amount of storage lipids in zygotic (Finkelstein and Somerville, 1989) as well as somatic (Kim and Janick, 1991) embryos. In cacao ZE, the effects of ABA and high sucrose are qualitatively similar, both increasing the amount of storage lipids (Pence, 1992). Both ABA and osmoticum are known to promote synthesis of a number of proteins in developing embryos (Skriver and Mundy, 1990), including storage protein.…”
Section: Introductionmentioning
confidence: 97%